Determination of the in situ mechanical behavior of ankle ligaments. (January 2017) - Nie, Bingbing; Panzer, Matthew B.; Mane, Adwait; Mait, Alexander R.; Donlon, John-Paul; Forman, Jason L.; Kent, Richard W.
Abstract: The mechanical behavior of ankle ligaments at the structural level can be characterized by force–displacement curves in the physiologic phase up to the initiation of failure. However, these properties are difficult to characterize in vitro due to the experimental difficulties in replicating the complex geometry and non-uniformity of the loading state in situ . This study used a finite element parametric modeling approach to determine the in situ mechanical behavior of ankle ligaments at neutral foot position for a mid-sized adult foot from experimental derived bony kinematics. Nine major ankle ligaments were represented as a group of fibers, with the force–elongation behavior of each fiber element characterized by a zero-force region and a region of constant stiffness. The zero-force region, representing the initial tension or slackness of the whole ligament and the progressive fiber uncrimping, was identified against a series of quasi-static experiments of single foot motion using simultaneous optimization. A range of 0.33–3.84 mm of the zero-force region was obtained, accounting for a relative length of 6.7±3.9%. The posterior ligaments generally exhibit high-stiffness in the loading region. Following this, the ankle model implemented with in situ ligament behavior was evaluated in response to multiple loading conditions and proved capable of predicting the bony kinematics accurately in comparison to the cadaveric response. Overall, the parametric ligament modeling demonstrated the feasibility of linking the gross structural behavior and the underlying bone and ligament mechanics that generate them. Determination of the in situ mechanical properties of ankle ligaments provides a better understanding of the nonlinear nature of the ankle joint. Applications of this knowledge include functional ankle joint mechanics and injury biomechanics. Graphical abstract: Highlights: Mechanical behavior of ankle ligaments controls the kinematic response of a foot. We used a parametric modeling approach to determine in situ ligament behavior. The optimal model proved capable of predicting bony kinematics and kinetics. The approach was feasible to link joint behavior and the underlying mechanics.